The state concept: the political thinking of Mohammad Natsir - Rusli, Ris’an (Penerbit Universiti Kebangsaan Malaysia, 2018)
State is an institution that accommodates the interests of individuals within the scope of community life. The concept of the state has a strategic role in determining various policies on all aspects including politics, society, economy, and education. In its journey, the form and concept of the state became a matter of debate and difference of views. One of the Muslim intellectuals providing views on the concept of the state is Mohammad Natsir. Natsir holds that the head of the state should be good person morally, democratically, constitutionally and has the support from the people. He offers the conception of a moral state and a clean government. He also discusses about the nature of the head of the state (imam), the need for the head of the state, the character of the head of the state, the appointment and determination of the head of the state, and also about his position on Indonesian’s Pancasila.